2008
DOI: 10.1021/ac800792g
|View full text |Cite
|
Sign up to set email alerts
|

Sample Zone Dynamics in Peak Mode Isotachophoresis

Abstract: We present a theoretical and experimental study of analyte preconcentration via peak mode isotachophoresis (ITP). We perform perturbation analysis of the governing equations that includes electromigration, diffusion, buffer reactions, and nonlinear ionic strength effects. This analysis relaxes the inherent numerical stiffness and achieves a fast solution to the transient sample evolution problem. In this model, we have incorporated a semiempirical relation to capture dispersion phenomenon within ITP interfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
173
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 97 publications
(185 citation statements)
references
References 34 publications
10
173
2
Order By: Relevance
“…Here we account for a semi-infinite injection mode, wherein both target and reporter molecules are mixed homogenously within the TE buffer and continuously focus into the ITP zone. 24 Experiment results are in good agreement with our numerical model ( Figure 2B; see the Supporting Information for a detailed description of the numerical simulations).…”
supporting
confidence: 85%
“…Here we account for a semi-infinite injection mode, wherein both target and reporter molecules are mixed homogenously within the TE buffer and continuously focus into the ITP zone. 24 Experiment results are in good agreement with our numerical model ( Figure 2B; see the Supporting Information for a detailed description of the numerical simulations).…”
supporting
confidence: 85%
“…The ITP interface width, δ, can be measured as a function of time from an ITP experiment focusing a fluorescent species. See Khurana et al (23) for general formulation of the analyte accumulation rate parameters V ITP , c LE , c TE well and ion mobilities. We numerically solve this set of non-linear ordinary differential equations (ODEs) for the volume averaged species concentrations to describe nucleic acid hybridization kinetics under ITP focusing.…”
Section: Resultsmentioning
confidence: 99%
“…For example, electrophoretic separations at high ionic strengths have been suggested to minimize peak distortion due to electromigration dispersion [14], and high ionic strength separations have also been used to reduce wall adsorption of cationic proteins [15] and increased analyte selectivity [16]. Other studies have reported on the adverse effects of high ionic strength, which may lead to zone reversal in CZE and ITP [17,18], and decreased focusing rate in ITP [19].…”
Section: General Aspectsmentioning
confidence: 99%
“…a ''semi-infinite sample'' configuration), the sample is mixed in the TE well (reservoir) and continuously overspeeds the TE ions to focus at the TE-LE interface. The TE and sample ions displace the LE ions and, in bulk liquid regions formerly occupied by LE ions, adjust to concentration levels dictated by the LE [19]. The sample concentration, C S,te , in the new ''regulated'' TE zone can be calculated from flux balance at the interface of TE well and regulated TE zone.…”
Section: Sample Preconcentration In Peak Mode Itpmentioning
confidence: 99%
See 1 more Smart Citation